Endocannabinoid-mediated long-term depression of afferent excitatory synapses in hippocampal pyramidal cells and gabaergic interneurons - Péterfi, Zoltán; Monyer, Hannah (The journal of neuroscience, 2012)
Although endocannabinoids have emerged as essential retrograde messengers in several forms of synaptic plasticity, it remains controversial whether they mediate long-term depression (LTD) of glutamatergic synapses onto excitatory and inhibitory neurons in the hippocampus. Here, we show that parvalbumin- and somatostatin/metabotropic glutamate receptor 1a (mGlu1a)-positive GABAergic interneurons express diacylglycerol lipase-α (DGL-α), a synthesizing enzyme of the endocannabinoid 2-arachidonoylglycerol (2-AG), albeit at lower levels than principal cells. Moreover, this lipase accumulates postsynaptically around afferent excitatory synapses in all three cell types. To address the role of retrograde 2-AG signaling in LTD, we investigated two forms: (1) produced by postsynaptic spiking paired with subsequent presynaptic stimulation or (2) induced by group I mGlu activation by (S)-3,5-dihydroxyphenylglycine (DHPG). Neither form of LTD was evoked in the presence of the mGlu5 antagonist MPEP [2-methyl-6-(phenylethynyl)-pyridine], the DGL inhibitor THL [N-formyl-l-leucine (1S)-1-[[(2S,3S)-3-hexyl-4-oxo-2-oxetanyl]methyl]dodecyl ester], or the intracellularly applied Ca2+ chelator BAPTA in CA1 pyramidal cells, fast-spiking interneurons (representing parvalbumin-containing cells) and interneurons projecting to stratum lacunosum-moleculare (representing somatostatin/mGlu1a-expressing interneurons). Both forms of LTD were completely absent in CB1 cannabinoid receptor knock-out mice, whereas pharmacological blockade of CB1 led to inconsistent results. Notably, in accordance with their lower DGL-α level, a higher stimulation frequency or higher DHPG concentration was required for LTD induction in interneurons compared with pyramidal cells. These findings demonstrate that hippocampal principal cells and interneurons produce endocannabinoids to mediate LTD in a qualitatively similar, but quantitatively different manner. The shifted induction threshold implies that endocannabinoid-LTD contributes to cortical information processing during distinct network activity patterns in a cell type-specific manner.